Transdermal liposomes for treatment of atopic dermatitis - Ong, Amanda Jiamin (2019)
Eczema, a skin chronic disorder, is a prevalent inflammatory skin disease. Current treatment methods include the use of systematic immunosuppressant, Cyclosporine and Azathioprine. In recent studies, Methotrexate (MTX) has shown to be a potential treatment of eczema. Indeed, there have been many studies done with regards to the encapsulation techniques of various drugs.